3D property objects in South African local government: the necessity of representing and managing the third dimension in the City of Cape Town property management system - Humby, Lara (School of Architecture, Planning and Geomatics, 2022)
The objective of this research was to analyse whether there is a need for a form of 3D Land Administration System (LAS)in South Africa (SA) based on the land administration functions of land tenure, land use, land development and land value. The investigation can be divided into two key focus areas that align with subsystems of the LAS: (i) the Land Tenure System (LTS) that is responsible for land tenure; and (ii) the Property Management System (PMS) that is responsible for land use, development and value. These two key areas fall within the SA LAS and make use of the cadastre as a foundation. Humby (2014) focussed on the first subsystem and found that there may be a significant need within the LTS for a 3D cadastral record or a 3D legal property object (LPO). The second subsystem is the focus of this study. To analyse the need for 3D in the PMS, the City of Cape Town (CCT) was adopted as a single case study, and modelled using systems thinking tools. The model focussed on the definition, use and management of property information, or the conceptual 3D property management object (PMO), to fulfil the land administration functions of land use, development and value within the CCT PMS. Established land administration theory, including the Land Management Paradigm, the good governance principles and RRR requirements, was used as a foundation against which the CCT PMS was analysed. This allowed for an increased understanding of the current CCT PMS's ability to achieve its land administration goals, policies and sustainable development. Following this, the current use of 3D within the CCT PMS was presented and analysed, along with the potential resulting benefits, uses and challenges of introducing 3D into that system. Semi-structured in-depth interviews, documentation evidence and participant and direct observations were employed in this section of the research. Furthermore, international land administration and 3D experiences, as presented in the literature review, were incorporated in this analysis. This study concludes that introducing a third dimension into the CCT PMS would have its challenges, but the uses and benefits that have been seen globally and that are recognised within the CCT, may outweigh those challenges. The research illustrates how a 3D Property Management Object would clarify the records and aid the land administration functions. Preferably, 3D would be introduced into the cadastre and LTS initially, and the PMS could then adopt that real RRRs LPO record as a foundation for the PMO records. However, the LTS has fallen behind in technology and it appears the CCT PMS will have to take the lead in introducing 3D into the SA LAS. It is recommended that a full cost-benefit analysis is conducted prior to any further research or development within the CCT.